Las P´s de Mercadeo Algunas precisiones (2019)
This article intends to clarify some misconceptions and misunderstandings in regard to the nature of the marketing variables and their classification, which may have implications both on the praxis and the development of the discipline. It addresses the concept of taxonomic classifications in marketing, i.e. nature, requirements, etc. and the dynamic nature of this discipline, which calls for a permanent updating of its models and classifications, in accordance with an ever changing environment.